دراسة السلوك الإجهادي التشوهي للترب الرملية المحقونة بالسيليكات - الزاوي منذر عمران (Latakia University Journal -Engineering Sciences Series, 2019)
إن حقن التربة الرملية المخلخلة بالسيليكات له أهمية تقنية واقتصادية خاصة في مجال الهندسة الجيوتكنيكية لأنه قليل الكلفة نسبيا فهو بسبب نفاذية الرمل لا يتطلب ضواغط معقدة لحقن المادة فضلا عن كفاءته في تلقي الحمولات, ويهتم هذا البحث بدراسة السلوك الإجهادي التشوهي للكتلة المتصلبة المركبة من الرمل ومادة الحقن (السيليكات) ومن أجل تحقيق هذه الغاية تم إجراء تجارب الزحف على عدد كبير من العينات المختبرة وتقييم نتائجها, واستنباط بارامترات الزحف بدلالة تغير الإجهادات المطبقة على العينات المختبرة, وأدخلت البارامترات المذكورة في القانون الريولوجي الخاص بموديل "كالفن المعمم" الذي تم اعتماده كموديل ريولوجي لدراسة سلوكية المادة المحقونة, ولدى مقارنة نتائج الحساب مع نتائج التجارب المخبرية تبين أن الموديل المعني يمكن اعتماده بدقة كافية لرسم منحنيات زحف خاصة بالتربة الرملية المحقونة وتوفير زمن وكلفة تجارب الزحف المخبرية ويبرهن إن معادلة التشوه المعتمدة صالحة لتبني قانون مادة جديد من أجل الحساب العددي للمنشآت المحقونة والمدعمة بطريقة العناصر المحددة . The injection of loose sandy soil with silicate has a technical and economical importance especially in the field of Geotechnical Engineering because of its low cost, and it does not need complex compressors to inject the material because of its high permeability of the sand as well as its efficiency in receiving loads. This research is interested in studying the deformation stress behaviour of the rigid sand-silicate mass. To realize this purpose, the creep experiments were done on a large number of tested samples and their results were evaluated and the creep pyrometers were taken out in terms of the stresses change applied on the tested samples. The previous pyrometers were entered in rheological law which is specialized in Popularized Calvin Model which is used as a rheological model to study the injected material behavior. It was noticed when the calculation results were compared with the laboratory experiments results that the previous model can be accurately adopted to draw special injected sand creep curves and to save the cost and the time of the laboratory creep experiments and it assures that the used deformation equation is valid for the adoption of a new material law for the numerical exact calculation of the injected and supported constructions with the FEM.